ISSUES OF FURTHER IMPROVING THE EFFICIENCY OF THE PROSECUTOR'S SUPERVISION OVER LAW ENFORCEMENT IN THE FIELD OF LAND IN THE REPUBLIC OF UZBEKISTAN - Mardonov Kamal Karomat Son (Journals Park Publishing, 2022)
This article examines the organizational and legal basis of the prosecutor's supervision over the implementation of legislation in the field of land in the Republic of Uzbekistan, the prevention of plundering of agricultural land, the role of the prosecutor's supervision in the use of land plots, and other issues.
Keywords: Prosecutor's control over the implementation of legislation in the field of land in the Republic of Uzbekistan, non-compliance with land legislation, purposeless and inefficient use of land plots